2008
DOI: 10.1902/jop.2008.070568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scaling and Root Planing on Alveolar Bone as Measured by Subtraction Radiography

Abstract: Scaling and root planing of diseased periodontal pockets can significantly increase radiographic alveolar bone density as demonstrated through the use of digital subtraction radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Few papers evaluated the results of NSPT on the ABD using computer analysis of the radiographs. Dubrez et al (7), Okano et al (8) and Hwang et al (9) reported that ABD increased significantly after NSPT, while Schmidt et al (6) did not find significant difference in the ABD after 2 years of observation. Hwang et al (9) were the authors whose method most closely resembled the one used in this study, Wilcoxon test was used to calculate the p value.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Few papers evaluated the results of NSPT on the ABD using computer analysis of the radiographs. Dubrez et al (7), Okano et al (8) and Hwang et al (9) reported that ABD increased significantly after NSPT, while Schmidt et al (6) did not find significant difference in the ABD after 2 years of observation. Hwang et al (9) were the authors whose method most closely resembled the one used in this study, Wilcoxon test was used to calculate the p value.…”
Section: Discussionmentioning
confidence: 97%
“…Dubrez et al (7), Okano et al (8) and Hwang et al (9) reported that ABD increased significantly after NSPT, while Schmidt et al (6) did not find significant difference in the ABD after 2 years of observation. Hwang et al (9) were the authors whose method most closely resembled the one used in this study, Wilcoxon test was used to calculate the p value. δ1 demonstrates statistically significant difference between baseline and 90 days post treatment (90AT); δ2 demonstrates statistically significant difference between baseline and 180 days post treatment (180AT).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has now emerged that even non-surgical periodontal treatment of intrabony defects may result not just in clinical improvements but also in radiographic bone fill of the bony defects [9,10]. As such, one could speculate that if the baseline radiograph of a periodontal regeneration study was taken before NSPT, the final outcome might have been influenced by both NSPT and periodontal regenerative surgery (PRS) (rather than just PRS).…”
Section: Introductionmentioning
confidence: 99%
“…Nonsurgical periodontal treatment usually leads to the formation of a long junctional epithelium [27] , and partial bone fill in an infrabony periodontal defect can also occasionally occur following careful SRP. Hwang, et al [28] reported an increase in bone density in sites with more than 3 mm vertical alveolar bone loss after SRP. Reduction of radiographic defect depth was a positively associated use of adjunctive antibiotics [29] .…”
Section: Discussionmentioning
confidence: 99%